Preoperative Low Prealbumin Is Associated With Recurrence in Patients With Stage II/III Gastric Cancer After Laparoscopic D2 Gastrectomy - Gao, Chun; Dan Zeng, Ci Dian; Tong, Yi Xin; Zhu, Li; Zhang, Sheng (Frontiers in Surgery, 2022)
Background: Recurrence after surgery indicates poor prognosis in patients with gastric cancer. The aim of this study is to explore predictive factors contributing to recurrence in stage II/III gastric cancer patients after laparoscopic D2 gastrectomy. Methods: This is a retrospective study from a single tertiary referral hospital. Patients diagnosed with gastric cancer who met the inclusion criteria were included in this study. Clinicopathological characteristics of the patients were collected. Patients were follow-up divided into recurrence group and no recurrence group. Predictive factors were investigated in univariate and multivariate analysis. Results: A total of 462 patients were included. The incidence of recurrence is 26.4% (122/462) among all patients. The most common pattern of recurrence is hematogenous recurrence. In multivariate analysis, independent predictive factors for recurrence were serum prealbumin level (p<0.001), prognostic nutritional index (p=0.001), CA19-9 (p<0.001), number of lymph node metastasis (p<0.001), signet-ring cell carcinoma (p=0.001), tumor deposit (p=0.001) and no/incomplete adjuvant chemotherapy (p<0.001). Conclusions: Our findings revealed that nutritional status was independent predictive factors leading to recurrence in gastric cancer patients after D2 gastrectomy. We suggest that patients with risk factors of recurrence should receive both nutritional support and intense surveillance.